ANALISA PROSES DESAIN FIGURE GUNDALA OLEH ST-WORKSHOP - Octavianus Bramantha (Universitas Mercu Buana, 2021)
The development of films in Indonesia is currently experiencing many improvements, especially films with the theme of superheroes or superheroes. This is based on the increasing number of films from Hollywood that are adapted from comics. The development of these films has attracted various producers, especially toys, to make collectible items, such as action figure toys. This is also Gundala did. In this study, the author aims to analyze the design process and production process of action figures made by ST Workshop, from how to adapt the character designs contained in the film to become a 16 cm figure.